Stretching and heating cells with light—nonlinear photothermal cell rheology. (12th August 2020) - Huster, Constantin; Rekhade, Devavrat; Hausch, Adina; Ahmed, Saeed; Hauck, Nicolas; Thiele, Julian; Guck, Jochen; Kroy, Klaus; Cojoc, Gheorghe
Abstract: Stretching and heating are everyday experiences for skin and tissue cells. They are also standard procedures to reduce the risk for injuries in physical exercise and to relieve muscle spasms in physiotherapy. Here, we ask which immediate and long-term mechanical effects of such treatments are quantitatively detectable on the level of individual living cells. Combining versatile optical stretcher techniques with a well-tested mathematical model for viscoelastic polymer networks, we investigate the thermomechanical properties of suspended cells with a photothermal rheometric protocol that can disentangle fast transient and slow 'inelastic' components in the nonlinear mechanical response. We find that a certain minimum strength and duration of combined stretching and heating is required to induce long-lived alterations of the mechanical state of the cells, which then respond qualitatively differently to mechanical tests than after weaker/shorter treatments or merely mechanical preconditioning alone. Our results suggest a viable protocol to search for intracellular biomolecular signatures of the mathematically detected dissimilar mechanical response modes.